1996
DOI: 10.1128/jb.178.1.240-247.1996
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the O antigen polymerase (rfc) gene in Escherichia coli O4 by insertional mutagenesis using a nonpolar chloramphenicol resistance cassette

Abstract: Computer analysis of the O4 polysaccharide gene cluster of Escherichia coli revealed the presence of two open reading frames (ORFs) encoding strongly hydrophobic polypeptides. O antigen polymerase, which is encoded by the rfc gene, is a potential membrane protein and therefore should be hydrophobic. To identify the rfc gene, these two ORFs were subjected to insertional mutagenesis. A chloramphenicol resistance cassette was designed which, when properly inserted, does not cause a polar effect in downstream gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 48 publications
0
35
1
Order By: Relevance
“…5, columns 4 and 9). In contrast, the presence of the promoterless cat cartridge (33) in the flp-1 flp-2 deletion mutant 35000HP.402 did not appreciably affect the levels of the tadB and tadG transcripts (Fig. 5, columns 2 and 7, respectively) in this mutant relative to those levels observed in the wild-type parent strain (Fig.…”
Section: Vol 70 2002 H Ducreyi Requires Flp For Microcolony Formatmentioning
confidence: 77%
See 1 more Smart Citation
“…5, columns 4 and 9). In contrast, the presence of the promoterless cat cartridge (33) in the flp-1 flp-2 deletion mutant 35000HP.402 did not appreciably affect the levels of the tadB and tadG transcripts (Fig. 5, columns 2 and 7, respectively) in this mutant relative to those levels observed in the wild-type parent strain (Fig.…”
Section: Vol 70 2002 H Ducreyi Requires Flp For Microcolony Formatmentioning
confidence: 77%
“…However, unlike the previous two mutants described above, this mutation was constructed in the human-passaged H. ducreyi strain 35000HP (6). A promoterless cat cartridge designed to permit transcription and translation of linked downstream ORFs (33) was inserted into a deletion that spanned part of both the flp-1 and flp-2 ORFs. Western blot analysis confirmed that this flp-1 flp-2 mutant lacked the ability to express the Flp1 and Flp2 proteins (Fig.…”
Section: Vol 70 2002 H Ducreyi Requires Flp For Microcolony Formatmentioning
confidence: 99%
“…Plasmid pUSPA1, which contains an incomplete uspA1 ORF from M. catarrhalis O35E (2) inserted into the multiple cloning site downstream from and in the same orientation as the plasmidbased lac promoter, was digested with BglII to remove a 0.6-kb internal fragment, and the BglII ends were then filled in with Pfu DNA polymerase using the manufacturer's recommended conditions. The resulting blunt-ended pUSPA1 plasmid was then ligated with a 706-bp SmaI fragment containing the promoterless cat gene from plasmid pSL1 (29). The ligation mixture was used to electroporate E. coli DH5␣, and recombinant clones were selected for resistance to chloramphenicol; the plasmids in these recombinants had the cat insert oriented in the same direction as the plasmid-based lac promoter.…”
Section: Methodsmentioning
confidence: 99%
“…The wzx coding sequence has an abundance of codons atypical for E. coli, suggesting that the Wzx protein is poorly translated. Lukomski et al (1996) showed that the wzy gene, which also contains an unusually high number of rare codons, cannot complement a wzy mutation when cloned in high-copynumber vectors. We then cloned the 5n6 kb EcoRI insert of pCM111 into the low-copy-number vector pSF6, resulting in plasmid pCM138 (Fig.…”
Section: Figmentioning
confidence: 99%